Editorial. Drawing in Artistic Research – Whence and Wherefore? - Barth, Theodor (FormAkademisk, 2018)
The topic of this special issue of FormAkademisk is drawing. While the issue is hosted by the Oslo National Academy of the Arts (KHiO), the contributors have come in from different urban locations in Norway, including Volda, Trondheim, Bergen and Oslo. We would like to use this occasion to extend our thanks to the external peer-reviewers. They have helped in bringing the issue to its present level of quality